Langston Hughes and the South African Drum Generation
VIII, 199 p.
Keywords: This collection combines previously unpublished letters between African-American poet Langston Hughes and South-African writers of the 1950s and 1960s with scholarly commentary and criticism. The letters tell a fascinating story of the civil rights movement and apartheid and the struggle to overthrow it.